ANALISIS DURABILITAS MORTAR GEOPOLIMER ABU SEKAM PADI TERHADAP ASAM SULFAT - zultonix Pratama; Abdi Nasrullah (JURNAL ILMIAH BERING'S, 2020)
This study aims to determine the resistance of rice husk geopolymer mortars to sulfuric acid. This research was conducted using experimental methods, namely by conducting experiments in the laboratory. Cuboid specimens measuring 50x50x50 mm, using binder: fine aggregate ratio is 1: 1.5, activator: precursor ratio 1: 1 and the ratio of Na2SiO3 and NaOH is 2: 1. Mortar immersed for 20 days with immersion of 5%, 10% and 15% sulfuric acid concentration. The compressive strength of the free geopolymer mortar is 9.20 MPa, sulfuric acid soaked with geopolymer mortar with a concentration of 5% is 5.00 MPa, immersion with a concentration of 10% is 4.60 MPa and immersion with a concentration of 15% is 2.00 MPa. From the compressive strength test results showed that there is a decrease in compressive strength of mortar exposed to sulfuric acid, the more concentrated sulfuric acid concentration, the lower the results of the geopolymer mortar compressive test results. This can be seen in the compressive strength concentration value of 5% decreased by 45.65%, the concentration of compressive strength of 10% decreased by 50.00% and the concentration of compressive strength of 15% decreased to 78.26%.